Predictors of Complete Response in Patients with Hepatocellular Carcinoma Treated with Trans-Arterial Radioembolization - Kim, Yuna (Curr Oncol, 2021)
Background: Trans-arterial radioembolization (TARE) has shown promising results in treating hepatocellular carcinoma (HCC). We identified independent predictors of radiological complete response (CR) in patients with intrahepatic HCC who were treated with TARE. Methods: Patients with intrahepatic HCC treated with TARE between 2011 and 2017 were recruited. CR was defined according to the modified Response Evaluation Criteria in Solid Tumors. Cox regression analysis was used to determine independent predictors of CR. Results: The median age of study participants (83 men and 19 women) was 64.3 years. The mean survival after TARE was 55.5 months, and 21 (20.6%) patients died during the study period. Patients who achieved CR (14 patients, 13.7%) had significantly higher serum albumin level (median 4.1 vs. 3.9 g/dL), lower total bilirubin level (median 0.6 vs. 0.7 mg/dL), lower aspartate aminotransferase level (median 30.0 vs. 43.0 IU/L), lower alkaline phosphatase level (median 79.0 vs. 103.0 IU/L), lower alpha-fetoprotein level (median 12.7 vs. 39.9 ng/mL), lower des-gamma-carboxyprothrombin level (median 575.5 vs. 2772.0 mAU/mL), lower model for end-stage liver disease (MELD) score (median 6.0 vs. 7.0), and smaller maximal tumor diameter (median 6.3 vs. 9.0 cm) compared to those who did not achieve CR (all p < 0.005). Multivariate Cox regression analysis showed that lower MELD score (hazard ratio (HR) = 0.436, p = 0.015) and maximal tumor size < 9 cm (HR = 11.180, p = 0.020) were independent predictors of an increased probability of radiological CR after TARE. Conclusions: Low MELD score and small maximal tumor size were independently associated with an increased probability of CR after TARE in patients with intrahepatic HCC.